2018
DOI: 10.1016/j.bbmt.2018.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Donor Age and Donor Relatedness on Time to Allogeneic Hematopoietic Cell Transplantation in Acute Leukemia

Abstract: Relapse after allogeneic hematopoietic cell transplantation (HCT) for acute leukemia can be reduced when pursued early after first complete remission. The impact of donor age and donor relatedness on the time from diagnosis to transplant in patients with acute leukemia was examined to clarify the design of future prospective studies that can address optimal donor choice. Files of 100 consecutive patients undergoing transplantation for leukemia were reviewed. Recipients of related donors (RDs) and unrelated don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…17 A 2018 paper by Visram et al found that unrelated donors for HCT for acute leukaemia were significantly younger than related donors (median age, 29 vs 51; P < 0.001), indicating a continued preference for younger unrelated donors. 18 A recent paper by Perales et al compared results of HCT for AML between recipients of haploidentical donors and matched unrelated donors aged 18-40 years, and found better survival for the unrelated donors, indicating that they were preferred. 19 The present study is limited by a relatively small patient population (n = 1158), a lack of available highresolution HLA typing, and a small number of HLA mismatched donors (n = 95), making conclusive statements about the effect of HLA compatibility difficult.…”
Section: Discussionmentioning
confidence: 99%
“…17 A 2018 paper by Visram et al found that unrelated donors for HCT for acute leukaemia were significantly younger than related donors (median age, 29 vs 51; P < 0.001), indicating a continued preference for younger unrelated donors. 18 A recent paper by Perales et al compared results of HCT for AML between recipients of haploidentical donors and matched unrelated donors aged 18-40 years, and found better survival for the unrelated donors, indicating that they were preferred. 19 The present study is limited by a relatively small patient population (n = 1158), a lack of available highresolution HLA typing, and a small number of HLA mismatched donors (n = 95), making conclusive statements about the effect of HLA compatibility difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is important because, from a practical standpoint, waiting for an URD for a patient with very high-risk or refractory disease is often a risky, or even unreasonable, option. Identifying a suitable URD usually takes longer than 2 months, even in high-income countries [63], which delays the transplantation procedure [64] and impairs the optimal timing for these urgent transplantations, whereas a haploidentical donor can be cleared for donation in just 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…When registrants are no longer interested or able to donate or where registries are unable to contact registrants, transplant centers are forced to look for other donor options, which can sometimes result in less favorable matches for the patients. This can introduce delays in the transplant process, place patients at increased risk of adverse outcomes, and limit the utility of unrelated donor registries 3,4 . Identifying registrant factors associated with availability for donation and for completing the required tests for initial donor consideration allows registries to adopt changes that will enhance the utility of their registry.…”
Section: Introductionmentioning
confidence: 99%